STRUCTURE OF EARTHQUAKE RESISTANT CONCRETE BUILDING WITH DUAL SYSTEM USING SNI 1726: 2019 - Novi Gita Apriliani; Tony Hartono Bagio (Neutron, 2020)
The higher a building, the greater the burden due to lateral forces. In the planning of the building structure of Apartment 88 Avenue Surabaya, a Dual system is used. This building planning is based on the Structural Concrete Requirements for Buildings (SNI 2847: 2019). And for earthquakes based on Earthquake Resilience Planning Procedures for Building and Non- Building Structures (SNI 1726: 2019 ). In the analysis of earthquake loads using dynamic analysis of the Response Specific Trump. The structure is planned to use reinforced concrete construction. The planning method includes the primary structure, namely the dimensioning and reinforcement of the main beam, and the column. And the secondary structure which consists of dimensioning and reinforcing plates, joists. From the results obtained structural design dimensional beam 35/70 cm ( 5D22; 3D22 ), the joist 30/55 cm ( 2D16; 2D16 ), the floor slab 14 cm thick ( D10-275 )